Responsible research and innovation: critical reflection into the potential social consequences of ICT - Eden, G; Jirotka, M; Stahl, B (IEEE, 2013)
The potential social consequences that may arise as a result of the development and widespread use of ICT are of increasing interest to the general public, policymakers and researchers. Prominent examples include transformations of our concept of privacy when using social networking and other websites, ownership and control of personal data, and the ways crowd-sourced information transform how events are coordinated and how they unfold in real-time. Although there is broad acceptance that questions of professional responsibility are relevant to ICT it is often unclear how this could be achieved or how responsibilities should be defined and managed when considering the potential social consequences of ICT. ‘Responsible Research and Innovation’ (RRI) has emerged in Europe proposing approaches for researchers to identify and consider the potential social consequences and impact of their research outputs within the entire research and innovation lifecycle. First, it asks researchers to take on a practice of critical reflection considering the potential societal impacts of their research outputs, and second to include the general public in a dialogue around the development of research goals and strategy. We discuss findings from interviews conducted with a broad range of stakeholders regarding challenges to identifying, debating and resolving social and ethical concerns associated with ICT research and practice. We also consider how we might extend existing or develop new approaches that facilitate both critical reflection and wider participation within the entire research and innovation lifecycle.